2019
DOI: 10.1002/elps.201900028
|View full text |Cite
|
Sign up to set email alerts
|

Ideal‐filter capillary electrophoresis: A highly efficient partitioning method for selection of protein binders from oligonucleotide libraries

Abstract: Selection of affinity ligands for protein targets from oligonucleotide libraries currently involves multiple rounds of alternating steps of partitioning of protein‐bound oligonucleotides (binders) from protein‐unbound oligonucleotides (nonbinders). We have recently introduced ideal‐filter capillary electrophoresis (IFCE) for binder selection in a single step of partitioning. In IFCE, protein‐binder complexes and nonbinders move inside the capillary in the opposite directions, and the efficiency of their partit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…The process of selection and enrichment is simplified when the separation between nonbinding and binding sequences is increased. A new technique called ideal filter capillary electrophoresis (IFCE) was introduced during the time frame of this Review. , IFCE overcomes limitations of CE-SELEX and NECEEM because the target–binder complex and nonbinding sequence migrate in opposite directions, which reduces the amount of nonbinding sequences present in the fraction containing the binding sequences. This is achieved by adjusting the ionic strength of the running buffer to decrease the electroosmotic flow to be within a specific range.…”
Section: Dna Aptamersmentioning
confidence: 99%
“…The process of selection and enrichment is simplified when the separation between nonbinding and binding sequences is increased. A new technique called ideal filter capillary electrophoresis (IFCE) was introduced during the time frame of this Review. , IFCE overcomes limitations of CE-SELEX and NECEEM because the target–binder complex and nonbinding sequence migrate in opposite directions, which reduces the amount of nonbinding sequences present in the fraction containing the binding sequences. This is achieved by adjusting the ionic strength of the running buffer to decrease the electroosmotic flow to be within a specific range.…”
Section: Dna Aptamersmentioning
confidence: 99%
“…The PCR amplification of the ssDNA-enriched pool obtained after every round of screening is essential in selecting aptamers by NECEEM. It is very difficult to obtain aptamers through single-round screening because their abundance in the random library is only 10 −6 -10 −9 (Le, Krylova, Kanoatov, et al, 2019;Le, Krylova, & Krylov, 2019b). Many unbound ssDNAs can leak out to the bound ssDNAs during partitioning, forming the background of free ssDNAs.…”
Section: Non-selexmentioning
confidence: 99%
“…Lisi et al obtained its aptamer after three rounds of non-SELEX screening combined with high-throughput sequencing (Lisi et al, 2018). The aptamer can recognize not only whole τ-441 but also τ-381, τ-352 and τ-383 (Le, Krylova, Kanoatov, et al, 2019;Le, Krylova, & Krylov, 2019b strength of running buffer. They found that complex velocity > 0 > free ssDNA velocity and k B /k N > 1.7 × 10 9 could be realized and the condition of one-step screening could be satisfied through adding 100 mM NaCl into running buffer when using MutS (pI = 6) as target.…”
Section: Non-selexmentioning
confidence: 99%
“…The measured K d,app was 40 nM, which could be achieved but with three rounds of CE-SELEX. Several follow up papers on IFCE have already been published describing further details and equilibrium constant and rate constant determinations . Overall, IFCE is an exciting technique for high efficiency selection of aptamers.…”
Section: Pre-equilibrium Acementioning
confidence: 99%